REKAYASA PENYIMPANAN UBI JALAR (Ipomoea batatas L.) DI DALAM TANAH DENGAN VARIASI ALAS TUMPUKAN SEBAGAI UPAYA UNTUK MEMPERTAHANKAN KUALITAS - , ERNI ZUARI ([Yogyakarta] : Universitas Gadjah Mada, 2013)
One of local commodities that can be processed into food products are tubers. Sweet potatoes (Ipomoea batatas L.) is one of plantsthathas a great potention in Indonesia. However, the storage method done by farmers at presenthas not able to extend the shelf life of sweet potatoes yet. The storage method that has been done by farmers can only keep the sweet potatoes in 7-12 days. This research is aimed to engineer the sweet potatoes storage with modified stacking in the ground, so it can extend beetâsshelf lifein term of the changes ofweightreduction, physical qualities, and chemical composition. In this research, sweet potatoes storage is done in a hole in the ground with the size 40cm x 40cm x 40cm and using some variation of cover and base that is stacking with straw, plastic straw, and sand straw. For control, it is exercised by storing in a plastic and open space. Parameters related such as weight, water level, texture are observed periodically at intervals of three days during storage. The change of the composition of substances before and after storage is evaluated to determine the success of the storage process. Based on parameters of the rate of the weightreduction of sweet potato, the best treatment is storage with plastic and straw treatment with the rate of decrease 0.31%/day and decrease the level of violence 0.018%/day. There were changes of chemical composition during storage even though the changes are not too much. The final evaluation shows that storage with stacking plastic straw treatment is the best result compared with other storagetreatments, control, and conventional storage that has been done. With doing modification, sweet potatoes can last up to 1 month of storage.